Pedagogical Culture of Teachers at Technical Universities for Safe Educational Process During the War in Ukraine. - Tverdokhliebova, Natalia; Yevtushenko Nataliіa (Educational Challenges, 2023)
The entire education system is currently undergoing structural changes, which are reflected in the increased use of digital and distance learning technologies. Pedagogical culture as a personal characteristic of a teacher acts as a means of implementing professional activities in the unity of goals, objectives, as well as means and results. Simultaneously, different types of pedagogical activity form the functional structure of culture. The main features of pedagogical activity should be its complexity and integrity, creative nature, a combination of collective activity and individual creativity of teachers, because the process of solving pedagogical goals and objectives is a technology of pedagogical activity that characterizes the mode of existence and functioning of the teacher’s pedagogical culture. Teaching in the context of the war in Ukraine involves the use of various forms of education with the introduction of digital technologies and tools to ensure the safety of all participants in the educational process and flexibility in time and space. This approach allows you to adapt educational content to the needs of students and the requirements of the curriculum. At the same time, it becomes important to choose an individual educational trajectory in which students can change and adapt their educational process. The purpose of this article is to analyze the content of the concept of pedagogical culture of teachers of technical universities in modern conditions, to determine the most convenient format of university education to ensure the safety of all participants in the educational process in a war in Ukraine. The methodology on which this article relies includes empirical methods (observation, conversation, dialogue), which are used in full-time and distance learning, and theoretical methods (analysis, synthesis, generalization, explanation, classification). Based on them, we will formulate practical recommendations for the introduction of digital technologies and tools to ensure high-quality education for students of technical universities in the modern conditions of Ukrainian society. The following results are achieved within the framework of our research: the analysis of the essence of the concept of "pedagogical culture" was carried out, the main features and criteria for its formation were identified, the conditions for the formation of the pedagogical culture of teachers of technical universities in war conditions were outlined and analyzed, a study was conducted to identify the most convenient form of university education using digital technologies and tools to ensure the safety of all participants in the learning process in modern conditions. The conclusions make it possible to state that, despite the difficult situation in the country, it is necessary to prepare students of technical universities for their further professional and personal careers, accompanied by lifelong learning. The combination of digital tools is often a successful response to rapidly changing environments and results in a flexible teaching and learning system. This requires mandatory interaction between students and teachers who act as mentors.